2013
DOI: 10.1155/2013/632893
|View full text |Cite
|
Sign up to set email alerts
|

Multiantibody Strategies for HIV

Abstract: Vaccination strategies depend entirely on the appropriate responsiveness of our immune system against particular antigens. For this active immunization to be truly effective, neutralizing antibodies (nAbs) need to efficiently counter the infectivity or propagation of the pathogen. Some viruses, including HIV, are able to take advantage of this immune response in order to evade nAbs. This review focuses on viral immune evasion strategies that result directly from a robust immune response to infection or vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…A subset of bNAbs, including VRC01, has been shown to block HIV-1 transmission by cell-associated virus (57). Two vaginal gel formulations have both completed phase 1 clinical trials: the Mabgel triple combination of 2F5, 2G12, and 4E10 (25) and 2G12 manufactured in a Nicotiana-based process (26). A phase 1 clinical trial to assess the safety of a vaginal film containing VRC01-N is ongoing (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of bNAbs, including VRC01, has been shown to block HIV-1 transmission by cell-associated virus (57). Two vaginal gel formulations have both completed phase 1 clinical trials: the Mabgel triple combination of 2F5, 2G12, and 4E10 (25) and 2G12 manufactured in a Nicotiana-based process (26). A phase 1 clinical trial to assess the safety of a vaginal film containing VRC01-N is ongoing (58).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenously delivered 2G12 (21) and 2F5 and 4E10 (21,22), as well as topically applied b12 (23,24), protected against simian-human immunodeficiency virus (SHIV) infection in challenge studies using rhesus and cynomolgus macaques. Both vaginal gel formulations of a triple MAb combination of 2F5, 2G12, and 4E10 (Mabgel) (25) and 2G12 manufactured in a Nicotiana-based process (26) have completed phase 1 clinical trials.…”
mentioning
confidence: 99%
“…Many of the new monoclonal antibodies against HIV (PGT121-PGT128) are almost 10-fold more potent than the recently described PG9, PG16 and VRC01, and 100-fold more potent that the original prototype HIV neutralizing antibodies (b12, 2G12, 4E10) (Walker et al, 2011; Hiatt et al, 2013). Analysis of the anti-HIV broadly neutralizing monoclonal antibodies (bnAbs) now available suggests that certain combinations of potent antibodies have superior coverage of the enormous diversity of global circulating viruses and should be sought in active or passive immunization regimes.…”
Section: Topical Antibodiesmentioning
confidence: 97%
“…A major drawback of mAbs is that they are specific to one epitope. Consequently, they are more vulnerable to immune escape from rapidly mutating viruses, and this has been observed with many other viruses such as influenza, HIV or SARS-CoV-2 [ 77 , 152 , 153 , 154 , 155 ]. In an experimental setting, Steeds et al showed that GP variants G74R, P330S and H407Y were capable of readily escaping the WHO research neutralisation standard KZ52.…”
Section: Strategies To Prevent Immune Escape From Neutralising Antibodiesmentioning
confidence: 99%